Metabolisme van 4-(2,4-dichlorofenoksi) bottersuur (4-(2,4-DB)) deur Emex Australis STEINH - Heÿl, H. A (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc (Agric)) -- University of Stellenbosch, 1971.